Loop-Mediated Isothermal Amplification (LAMP): Emergence As an Alternative Technology for Herbal Medicine Identification - Li, Jing-jian; Xiong, Chao; Liu, Yue; Liang, Jun-song; Zhou, Xing-wen (Frontiers in Plant Science, 2016)
Correct identification of medicinal plant ingredients is essential for their safe use and for the regulation of herbal drug supply chain. Loop-mediated isothermal amplification (LAMP) is a recently developed approach to identify herbal medicine species. This novel molecular biology technique enables timely and accurate testing, especially in settings where infrastructures to support polymerase chain reaction facilities are lacking. Studies that used this method have altered our view on the extent and complexity of herbal medicine identification. In this review we give an introduction into LAMP analysis, covers the basic principles and important aspects in the development of LAMP analysis method. Then we presented a critical review of the application of LAMP-based methods in detecting and identifying raw medicinal plant materials and their processed products. We also provide a practical standard operating procedure (SOP) for the utilization of the LAMP protocol in herbal authentication, and consider the prospects of LAMP technology in the future developments of herbal medicine identification and the challenges associated with its application.